PRINSIP KESANTUNAN BERBAHASA DALAM NOVEL TAKBIR CINTA DI JABAL RAHMAH KARYA ROIDAH - Fidyanti, Dita; Patriantoro, Patriantoro; Amir, Amriani (Universitas Tanjungpura, 2024)
This study was conducted to describe the adherence to the principle of language politeness contained in the dialog in the novel Takbir Cinta di Jabal Rahmah by Roidah, as well as the implementation of this research in Indonesian language learning. This research uses a descriptive method by using a qualitative approach. The main data source used in this research is the novel Takbir Cinta di Jabal Rahmah by Roidah. The main data in this research is the compliance of the principles of language politeness in the dialog in the novel Takbir Cinta di Jabal Rahmah. The data collection technique used a documentary study technique. Data collection tools are researchers themselves and other tools. The techniques for testing the validity of this research are observation persistence, investigator triangulation, and using reference materials. Data analysis techniques used in this research are data reduction, data presentation, and conclusion drawing. This study found 53 utterances that contain the principle of language politeness according to Leech. It is described as 53 utterances of maxims of compliance which include: maxims of wisdom (12), maxims of generosity (1), maxims of praise (18), maxims of humility (5), maxims of agreement (15) and maxims of sympathy (2).